BOND MARKET DEVELOPMENT, AND INFRASTRUCTURE GROWTH IN AFRICA: EXAMINING THE MODERATING ROLE OF GOVERNMENT EFFECTIVENESS - Betty Tumuhirwe Tuhaise; Eric Nzibonera; Kiwala Yusuf; Jude Thadeo Mugarura; Onen David (ADVANCED INTERNATIONAL JOURNAL OF BANKING, ACCOUNTING AND FINANCE (AIJBAF), 2025)
Purpose: The main objective of the study was to establish the moderating role of government effectiveness on the relationship between bond market development, and infrastructure growth in Africa. Design/Methodology/Approach: The study used correlational research design, quantitative approach, parametric tests, and the Generalized Method of Moments (GMM) model to examine the relationship between infrastructure growth, bond market development, and government effectiveness in 53 African countries from 2013 to 2022. Used data from the World Bank, and the African Development Bank whose respective measures included the volume of bonds for bond market development, Indices for government effectiveness and infrastructure growth. Findings: The correlation between Portfolio investment bonds, and infrastructure development is positive but statistically insignificant with 0.00436 and statistically significant with the coefficient of energy of 0.0458** at 5% level of confidence, and the moderator enhances them to 0.00528*, 0.0435** at 10 and 5 % levels of confidence respectively. Research Limitations/Implications: The study limited itself on Africa’s physical infrastructure development, portfolio investment bonds, and government effectiveness. Practical Implications: It provided policy recommendations to enhance bond markets’ role in infrastructure financing. Future studies could explore alternative indicators for government effectiveness and bond types for bond market development. Social Implications: By focusing on physical infrastructure financing as a key social benefit, this study highlights areas for future research on soft infrastructure, and other hard physical infrastructure other than the one studied in this paper. Originality/Value: This study is among the first to examine government effectiveness as a moderator in the bond market–infrastructure growth relationship in Africa, using portfolio investment bonds, and the system GMM model. Plain Summary: Infrastructure development is vital for improving quality of life. This study demonstrates, for the first time, on how portfolio investment bonds can drive infrastructure growth in Africa, moderated by government effectiveness.